2014
DOI: 10.1016/j.celrep.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin-Mediated Gene Silencing Facilitates the Diversification of Olfactory Neurons

Abstract: SUMMARY An astounding property of the nervous system is its cellular diversity. This diversity, which was initially realized by morphological and electrophysiological differences, is ultimately produced by variations in gene expression programs. In most cases these variations are determined by external cues. However, a growing number of neuronal types have been identified in which inductive signals cannot explain the few but decisive transcriptional differences that cause cell diversification. Here, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 39 publications
(53 reference statements)
5
60
1
Order By: Relevance
“…Specifically in the nervous system, loss of G9a function led to increased cell proliferation and disorganized layering in the retina (Katoh, Yamazaki, Onishi, Sanuki, & Furukawa, 2012), and also resulted in a switch of neuronal subtypes, from dopamine receptor D2 expressing (Drd2) neurons to Drd1 neurons in the mouse nucleus accumbens (NAc) (Maze et al, 2014). Finally, GLP and G9a govern the heterochromatic silencing of olfactory receptor genes, which is essential for the diversification of olfactory neurons (Lyons et al, 2014). Overall these studies identified GLP and G9a as a crucial repressive complex during development and neuronal cell differentiation.…”
Section: The Repressive Complex Glp/g9amentioning
confidence: 98%
“…Specifically in the nervous system, loss of G9a function led to increased cell proliferation and disorganized layering in the retina (Katoh, Yamazaki, Onishi, Sanuki, & Furukawa, 2012), and also resulted in a switch of neuronal subtypes, from dopamine receptor D2 expressing (Drd2) neurons to Drd1 neurons in the mouse nucleus accumbens (NAc) (Maze et al, 2014). Finally, GLP and G9a govern the heterochromatic silencing of olfactory receptor genes, which is essential for the diversification of olfactory neurons (Lyons et al, 2014). Overall these studies identified GLP and G9a as a crucial repressive complex during development and neuronal cell differentiation.…”
Section: The Repressive Complex Glp/g9amentioning
confidence: 98%
“…OR genes bear histone marks characteristic of constitutive heterochromatin in sustentacular cells, yet OR genes remain dispersed (Clowney et al 2012, Magklara et al 2011). OR genes are not heterochromatinized in G9a–GLP knock-out mice, but OR foci still form, although they are not as well organized as in wild-type OSNs (Lyons et al 2014). …”
Section: Does Nuclear Organization Coordinate Olfactory Receptor Choice?mentioning
confidence: 99%
“…Remarkably, blocking the formation of H3K9me3-marked heterochromatin has a dramatic effect on the pattern of OR expression (Lyons et al 2014). Blocking H3K9me3 formation has been accomplished by conditionally deleting two histone methyltransferases, G9a and GLP, that generate H3K9me2, a necessary precursor of H3K9me3.…”
Section: Chromatin-mediated Silencing Of Olfactory Receptor Genes Ismentioning
confidence: 99%
“…Recent data from our lab demonstrated that loss of heterochromatic silencing from the OR cluster by the simultaneous deletion of H3K9 methyltransferases G9a and G9a-like ( Glp ) results in expression of only a few OR genes instead of the full repertoire. Thus, without chromatin-mediated silencing, it appears that the random selection of an OR allele is substituted by the selective choice of a few alleles that dominate the olfactory epithelium and are expressed in a nonmutually exclusive fashion (Lyons et al 2014). …”
Section: The Main Olfactory Epithelium: Olfactory Receptorsmentioning
confidence: 99%